Scorpions and life-history strategies: from evolutionary dynamics toward the scorpionism problem - Lourenço,Wilson R. (2018)
Abstract This work aims to contribute to the general information on scorpion reproductive patterns in general including species that can be noxious to humans. Scorpions are unusual among terrestrial arthropods in several of their life-history traits since in many aspects their reproductive strategies are more similar to those of superior vertebrates than to those of arthropods in general. This communication focuses mainly on the aspects concerning embryonic and post-embryonic developments since these are quite peculiar in scorpions and can be directly connected to the scorpionism problem. As in previous similar contributions, the content of this communication is addressed mainly to non-specialists whose research embraces scorpions in several fields such as venom toxins and public health. A precise knowledge of reproductive strategies presented by several scorpion groups and, in particular, those of dangerous species may prove to be a useful tool in the interpretation of results dealing with scorpionism, and also lead to a better treatment of the problems caused by infamous scorpions.